KUALITAS PELAYANAN, FASILITAS HOUSEKEEPING DAN PENGARUHNYA TERHADAP KEPUASAN TAMU DI HOTEL GRAN PURI MANADO - Jeskrispen Lagarense; Tedy Valens Silape; Jelly Netty Sendow; Hiskia Damongilala (Jurnal Hospitaliti, 2025)
The hospitality industry is facing increasingly intense competition, making service quality and facilities key factors in maintaining guest satisfaction. This study aims to analyze the effect of service quality and housekeeping facilities on guest satisfaction at Gran Puri Hotel Manado. This research employs a quantitative approach using a survey method. The research population consists of guests staying at Gran Puri Hotel Manado, with a sample of 40 respondents selected through purposive sampling. The results indicate that: (1) service quality has a positive and significant effect on guest satisfaction, with a calculated t-value of 3.0766 > t-table 2.050 and a significance value of 0.015 < 0.05; (2) housekeeping facilities have a positive and significant effect on guest satisfaction, with a calculated t-value of 4.177 > t-table 2.050 and a significance value of 0.000 < 0.05; (3) service quality and housekeeping facilities simultaneously have a significant effect on guest satisfaction, with a calculated F-value of 484.521 and a significance value of 0.000 < 0.05. The adjusted R² value of 0.748 indicates that 74.8% of the variation in guest satisfaction can be explained by the two independent variables. Therefore, the hotel is recommended to continuously improve service quality through employee training and to enhance housekeeping facilities in accordance with appropriate standard operating procedures to increase guest satisfaction.